7 Proceedings and Acts of the General Assembly, October 1678-November 1683, at 53 (1889); see also 1698 Md. Acts 99 - (:unkn) unknown (My University, 1678)
Kept the militia ages "between sixteen and sixty yeares of age." Further required that each "appeare and bring with him one good serviceable fixed Gunn and six shoots of Powder." Troopers were required to bring their own horses, and "to find themselves with sword Carbine Pistolls Holsters & Amunition."
Keywords: MILITIAS; REQUIRED POSSESSION